2012
DOI: 10.1089/scd.2011.0259
|View full text |Cite
|
Sign up to set email alerts
|

HOXA4Induces Expansion of Hematopoietic Stem Cells In Vitro and Confers Enhancement of Pro-B-Cells In Vivo

Abstract: Members of the homeobox (Hox) gene family are known to mediate expansion of hematopoietic stem cells (HSCs) and progenitors. The absence of oncogenic properties promoted HOXB4 as prime candidate in the quest to expand HSCs for clinical purposes. Despite its potential to expand HSCs, studies with mutant mice showed that Hoxb4 is not essential for HSC generation and function under physiological conditions. Expression studies and the existence of functional redundancy in particular between paralog Hox genes sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…This was accompanied with expansion of total bone marrow (BM) cultures by HOXA4 that were up to 100-fold more important than control after 3 weeks of culture [6], and were comparable to earlier reported expansions with HOXB4-overexpressing progenitor cells [7]. The capacity to expand primitive hematopoietic cells appeared to be attributed to all paralog four members as evidenced in an embryonic stem cell overexpression model [8].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…This was accompanied with expansion of total bone marrow (BM) cultures by HOXA4 that were up to 100-fold more important than control after 3 weeks of culture [6], and were comparable to earlier reported expansions with HOXB4-overexpressing progenitor cells [7]. The capacity to expand primitive hematopoietic cells appeared to be attributed to all paralog four members as evidenced in an embryonic stem cell overexpression model [8].…”
Section: Introductionsupporting
confidence: 86%
“…Our group recently demonstrated that overexpression of HOXA4, which is highly homologous to HOXB4, also led to a net expansion of functional mouse HSC in vitro [6]. This was accompanied with expansion of total bone marrow (BM) cultures by HOXA4 that were up to 100-fold more important than control after 3 weeks of culture [6], and were comparable to earlier reported expansions with HOXB4-overexpressing progenitor cells [7].…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…HOXA4 overexpressing HSC expanded 6.6-fold after a week of culture. Although HOXA4 expressing HSC produced mature myeloid and lymphoid progeny in irradiated recipient mice, B-cell progenitors were preferentially expanded compared to myeloid progenitors (Fournier et al, 2011).…”
Section: Other Hox Family Proteinsmentioning
confidence: 97%